The Fruit Fly Protect project and its actions regarding the evaluation of different traps and attractants for Ceratitis capitata Wied. in Azores - Lopes, David João Horta (2022)
The Mediterranean fruit fly (Ceratis capitata Wiedemann) (Diptera: Tephritidae) is one of the most important pests for fruit and vegetable production because of its ability to damage fruits and adapt to new environments. This study aimed to compare different traps, namely Cera Trap® (Bioiberica) filled with food attractant and Tephri trap baited with Econex Trypack® for C. capitata monitoring. C. capitata adults were collected during three years (2018–2020) in citrus orchards on three different islands of the Azorean archipelago: Terceira, S. Miguel and S. Jorge. The results show only a statistical difference in 2020 for São Miguel Island in Tephri Trap. Cera Trap showed good results in terms of capture when population densities are high and it is, therefore, a good tool to control this pest but at low C. capitata densities, Tephri trap with Trypack represents a good control device.